A threshold trajectory was revealed by isolating the effects of hemoglobin rate of rise in anemia of chronic kidney disease. (October 2017) - Fusco, Gregory; Hariri, Ali; Vallarino, Carlos; Singh, Ajay; Yu, Peter; Wise, Lesley
Background: To assess cardiovascular risk among various hemoglobin (Hb) rates of rise (RoR) in chronic kidney disease (CKD) patients with anemia who have initiated therapy with erythropoiesis stimulating agents (ESAs). Methods: Observational cohort of CKD patients initiating ESA therapy from the Centricity ® database, 1990–2011. Proportional hazards models tested the hypothesis that a slower Hb RoR (0 < g/dl/month ⩽ 0.125) is associated with a lower cardiovascular (CV) incidence [composite of fatal/nonfatal myocardial infarction (MI) and stroke] compared with faster RoR (0.125 < g/dl/month ⩽ 2.0, and >2.0 g/dl/month). Results: A total of 9220 patients receiving ESAs were followed for an average of 3.1 years. Slow (group B) RoR versus medium (group C′) and fast (group D′) RoR in Hb, throughout all Hb milestones, was associated with lower risk of the composite endpoint [B (slow) versus D′ (fast) [hazard ratio (HR) = 0.20 (0.11, 0.39), p < 0.0001]; B versus C′ (medium) [HR = 0.34 (0.19, 0.62), p = 0.0004], and C′ versus D′ [HR = 0.60 (0.42, 0.85), p = 0.005]]. Within achieved Hb milestones, HRs were: B versus D′ at milestone ⩾ 14.1 g/dl [HR = 0.17 (0.05, 0.56); p = 0.004] and at milestone 12.6−14.0 [HR = 0.18 (0.07, 0.46), p = 0.0004]. Conclusion: Rapid Hb rise is associated with adverse CV outcomes, with markedly lower risk for rates below a threshold trajectory of 0.125 g/dl/month, even with complete correction.